PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DEVIDEN, PROFITABILITAS, LEVERAGE FINANCIAL, DAN INVESTMENT OPPURTUNITY SET TERHADAP NILAI PERUSAHAAN - SENDA, FRANSISKA DHORU (Universitas Katolik Widya Mandala Surabaya, 2013)
Financial management is one of the strategic functions that is highly related to management of finance. This administration allows the company to generate profits in order to optimize the organization’s value through the increase of shareholder’s wealth. The purpose of this study is to examine the effect of variable managerial ownership, institutional ownership, dividend policy, profitability, financial leverage and investment opportunity set of the firm’s value in companies listed in Bursa Efek Indonesia (Indonesia Stock Exchange). This study utilized purposive sampling criteria, which was retrieved from 28 companies eligible to be sampled. The sample in this study were retrieved from companies listed in Bursa Efek Indonesia (Indonesia Stock Exchange) during 2009-2011 period. The type of analysis being used in this study is panel data regression. The result of this study indicated that dividend policy, profitability and financial leverage has a positive effect on the firm’s value for the manufacturing company listed in Bursa Efek Indonesia (Indonesia Stock Exchange). On the other hand, managerial ownership, institutional ownership and investment opportunity set do not affect the firm’s value for the manufacturing company listed in Bursa Efek Indonesia.